Factors Analysis Which Influence Dividend Payment on Manufacture Company that Listed on Indonesia Stock Exchange - Vista Yuniarti Sitanggang; Yeni Agustina (Politeknik Negeri Lampung, 2011)
This research aims to examine empirically factors which influence dividend per share. This research used sample manufacture company that listed on indonesia stock exchange in 2005 – 2008. This analysis used dividend per share as dependent variable and liquidity ratio, growth ratio, DPSmin1, activity ratio and company size. This research used linear regression testing with SPSS program. Result of reasearch indicated that growth ratio and DPSmin1 gave positive effect and significant to dividend per share whereas liquidity ratio, growth ratio, activity ratio and company size did not give significant effect to dividend per share Key words: Divident per share, current ratio, DPSmin1, earning per share, total asset turn over and company size